PENGARUH KONTEN MARKETING DAN ENDORSEMENT TERHADAP MINAT BELI KONSUMEN PADA PRODUK PANCONG LUMER ALBIM KOTA BENGKULU - Bima Setyawan; Islamuddin Islamuddin (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
This study aims to determine which factors are most dominant in influencing consumer buying interest, the study was conducted from February to April 2025. The sample of this study was Pancong Lumer Albim Products in Bengkulu City. This study uses a quantitative method on 65 respondents. The sampling technique is probability sampling, the method used in this study is a quantitative method with Multiple Linear Regression analysis using SPSS 24 for windows. Based on the results of multiple linear regression, the regression equation form is Y = 3.731 + 1.757 (X_1) + 1.423 (X2) and the coefficient of determination R Square (R2) is obtained at 0.732 or 73.2%. The results of the study and the hypothesis in this study indicate that the variables of marketing content and endorsement have a positive effect, both partially and simultaneously, on consumer purchasing interest in Pancong Lumer Albim Products in Bengkulu City. Keywords: Marketing content, endorsement and purchasing interest.